Top 10 techno-cool cars. - Ross, P. (IEEE spectrum)
In IEEE Spectrum's list of top technocars, we preferred ideas expressed in a unique exemplar, preferably a vehicle from the current or the upcoming model year. We looked for significant jumps in performance, convenience, or comfort, rather than the incremental improvements that, chained together, account for most automotive progress over the long haul. We favored bold technologies, knowing full well that some might not trickle down to the family sedan for many years, if ever. The cars featuring on the list are: the Volvo Safety Concept Car; Saab-93; Honda Civic GX; Honda FCX; Cadillac XLR; Audi A8; Mercedes-Benz SL500; Fiat Stilo; Chevrolet Trailblazer; and Toyota Prius. The technologies include: Bluetooth wireless technology (Saab); natural gas and fuel cell vehicles (Honda); electrorheological fluid based suspension (Cadillac); computer control (Audi); braking by wire (Mercedes-Benz); smokeless diesel (Fiat); and hybrid vehicle (Toyota).